Mitochondrial Dynamics: Pathogenesis and Therapeutic Targets of Vascular Diseases - Luan, Yi; Ren, Kai-Di; Luan, Ying; Chen, Xing; Yang, Yang (Frontiers in Cardiovascular Medicine, 2021)
Vascular diseases, particularly atherosclerosis, are associated with high morbidity and mortality. Endothelial cell (EC) or vascular smooth muscle cell (VSMC) dysfunction leads to blood vessel abnormalities, which cause a series of vascular diseases. The mitochondria are the core sites of cell energy metabolism and function in blood vessel development and vascular disease pathogenesis. Mitochondrial dynamics, including fusion and fission, affect a variety of physiological or pathological processes. Multiple studies have confirmed the influence of mitochondrial dynamics on vascular diseases. This review discusses the regulatory mechanisms of mitochondrial dynamics, the key proteins that mediate mitochondrial fusion and fission, and their potential effects on ECs and VSMCs. We demonstrated the possibility of mitochondrial dynamics as a potential target for the treatment of vascular diseases.